Synthesis of lanthanum tungstate interconnecting nanoparticles by high voltage electrospinning - Yanee Keereeta (2018)
© 2015 Elsevier B.V. Lanthanum tungstate (La 2 (WO 4 ) 3 ) interconnecting nanoparticles in the shape of fibers were successfully synthesized by electrospinning in combination with high temperature calcination. In this research, calcination temperature for the synthesis of the fibers evidently influenced the diameter, morphology and crystalline degree. The crystalline monoclinic La 2 (WO 4 ) 3 fibers with 200–700 nm in diameter, two main Raman peaks at 945 and 927 cm −1 , FTIR stretching modes at 936 and 847 cm −1 , 2.02 eV energy gap and 415–430 nm blue emission were synthesized by calcination of inorganic/organic hybrid fibers at 750 °C for 5 h, characterized by X-ray diffraction, scanning electron microscopy (SEM), transmission electron microscopy (TEM), selected area electron diffraction (SAED), thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, UV–visible spectroscopy and photoluminescence (PL) spectroscopy. The surface of the composite fibers before calcination was very smooth. Upon calcination the composite fibers at 750 °C for 5 h, they were transformed into nanoparticles join together in the shape of fibers with rough surface.